Genomes of nitrogen-fixing eukaryotes reveal an alternate path for organellogenesis - Sarah Frail; Melissa Steele-Ogus; Jon Doenier; Solène L. Y. Moulin; Tom Braukmann; Shouling Xu; Ellen Yeh (Proceedings of the National Academy of Sciences, 2025)
Endosymbiotic gene transfer (EGT) and import of host-encoded proteins have been considered hallmarks of organelles necessary for stable integration of two cells. However, newer endosymbiotic models have challenged the origin and timing of such genetic integration during organellogenesis. Epithemia diatoms contain diazoplasts, obligate endosymbionts derived from cyanobacteria that are closely phylogenetically related to UCYN-A, a recently described nitrogen-fixing organelle. Diazoplasts function as permanent membrane compartments in Epithemia hosts, but it is unknown if genetic integration has occurred. We report genomic analyses of two Epithemia diatom species, freshwater Epithemia clementina and marine E. pelagica , which are highly divergent but share a common ancestor at the origin of the endosymbiosis <35Mya. We find minimal evidence for genetic integration. Segments of fragmented and rearranged DNA from the diazoplast were detected integrated into the E. clementina nuclear genome, but the transfers that have occurred so far are nonfunctional. No DNA or gene transfers were detected in E. pelagica. In E. clementina , 6 host-encoded proteins of unknown function were identified in the diazoplast proteome, far fewer than detected in recently acquired endosymbiotic organelles. Overall, Epithemia diazoplasts are a valuable counterpoint to existing organelle models, demonstrating that endosymbionts can function as integral compartments—maintained over millions of years of host speciation—absent significant genetic integration. The minimal genetic integration makes diazoplasts valuable blueprints for bioengineering endosymbiotic compartments de novo.